Study on the creep behaviors of a biodegradable Zn-1Mg-xCu alloy - Wenyuan Feng; Xiaohao Sun; Jingjun Gao; Debao Liu (Journal of Materials Research and Technology, 2025)
Zn alloys have emerged as a promising new class of degradable metal materials due to their favorable degradation rate, excellent biocompatibility, osteogenic function and non-toxic degradation products. However, the melting point of Zn-based alloys is relatively low. Under the physiological environment of body temperature, they will undergo creep deformation and even fail due to creep, which will affect the mechanical stability and safety of Zn-based implant materials. Currently, there is limited research on the creep behavior of biodegradable Zn alloys, especially under the combined effects of constant force and corrosion in simulated body fluids (SBF). This study evaluates the creep behavior (in air and SBF) of a biodegradable Zn–1Mg-xCu alloys (x = 0, 1, 2 wt%). The results show that due to the limited dislocation storage capacity in fine grains, the creep rupture duration of Zn–1Mg–2Cu alloy under a stress of 136 MPa were respectively 16.75 h in SBF and 71.95 h in air. Under the same stress, the creep rupture duration in SBF and air were 24.50 h and 89.35 h for Zn–1Mg, and 54.14 h and 227.66 h for Zn–1Mg–1Cu, respectively. Creep mechanisms shift from intragranular deformation in Zn–1Mg and Zn–1Mg–1Cu to grain boundary sliding in Zn–1Mg–2Cu. Creep failure in air is due to internal voids, while in SBF, it is caused by corrosion cracks on the material's surface. Regulating alloy element content and grain size will be an effective method to improve creep properties of Zn-based materials.